Effect of sodium hypochlorite and five intracanal medications on Candida albicans in root canals - Valera, Marcia Carneiro; Rego, Juliana de Moraes; Jorge, Antonio Olavo Cardoso [UNESP] (Lippincott Williams & Wilkins, 2001)
The aim of this study was to evaluate the effect of 1% sodium hypochlorite and five intracanals medications on Candida albicans harvested inside root canals. The contaminated canals were irrigated with sterile saline solution and then treated as follows: (i) filled with Calen paste (calcium hydroxide/glycol polyethylene paste); (ii) filled with camphorated paramonochloro phenol (CPMC); (iii) filled with 2% iodine-iodate solution; (iv) filled with tricresol formalin; (v) filled with Calen and CPMC pastes; (vi) irrigation with 1% sodium hypochlorite and filled with no intracanal medication; and (vii) no intracanal medication was used. Canal access and the apical foramen were then sealed with Cavit and the roots were stored in a humid chamber at 37 +/- 1 degreesC for 14 days. The canals were reinstrumented and irrigated with sterile saline solution. Sterile paper points were used to transfer the root canal contents to test tubes containing sterile saline solution. Part of the suspension was harvested in Sabouraud dextrose agar with chloramphenicol and incubated at 37 +/- 1 degreesC for 48 h, CPMC was effective in 100% of the samples followed in decreasing order of effectiveness by calcium hydroxide with CPMC (70% effective), 1% sodium hypochlorite (70% effective) (p < 0.05), tricresol formalin (60% effective), 2% iodine-iodate solution (50% effective), calcium hydroxide paste (30% effective), and saline + no intracanal medication.